Potret kepatuhan pasien hipertensi dalam mengonsumsi obat antihipertensi di Desa Banaran tahun 2024 - Bunga Mar’atus Sholikhah; Amama Yuniana Nurul Mustafidah (Journal of Health and Therapy, 2025)
Hypertension treatment takes a long time, so patient compliance during treatment is one of the basic things to do. This study aims to determine the relationship between gender and compliance with taking antihypertensive medication in hypertension sufferers in Banaran village, Geger subdistrict, Madiun district. This research method is an analytical-observational study with a cross-sectional design. This research was conducted in Banaran village and was carried out on 27-28 June 2024. The population of hypertension sufferers in Banaran village was 130, with a sample of 98, and the sampling technique was random sampling. The data analysis used is univariate and bivariate. Data processing used the Chi-Square statistical test with a significance level of 95% (0.05). The research results showed that there was no relationship between gender and compliance with taking antihypertensive medication in hypertension sufferers in Banaran village. Health facilities or related parties can provide education to hypertension sufferers in the local area so that awareness of paying more attention to health by taking medication for hypertension sufferers increases.